Hard carbon negative electrode material, preparation method thereof, negative electrode sheet and sodium ion battery
Patent Information
- Application Number
- CN202611285366.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-30
AI Technical Summary
该类方法虽在一定程度上改善了材料的动力学特性,但金属掺杂效率极低,仅能在碳层表面发生少量金属原子取代,无法实现体相均匀掺杂;同时,在充放电过程中,碳层表面金属颗粒的膨胀效应与副反应难以有效控制,反而劣化了长期循环稳定性,难以满足实际应用与规模化生产的需求
[0020]与现有技术相比,本申请的有益效果包括:
Smart Images

Figure CN123017934A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of sodium-ion batteries, and more particularly to a hard carbon anode material and its preparation method, an anode sheet, and a sodium-ion battery. Background Technology
[0002] Sodium-ion batteries have attracted widespread attention in the field of electrochemical energy storage due to their significant advantages, such as abundant sodium resources and low cost. To meet increasingly diverse application demands, sodium-ion batteries are continuously expanding their performance boundaries at low temperatures, striving for wider application in scenarios such as new energy vehicles and large-scale energy storage. Hard carbon, as one of the most commercially promising anode materials for sodium-ion batteries, plays a crucial role in optimizing its electrochemical performance, which directly affects the overall performance of the battery system.
[0003] However, traditional strategies for controlling the microstructure of hard carbon have reached a bottleneck, with a clear constraint between rate performance and specific capacity: improving rate performance often comes at the cost of sacrificing specific capacity, and vice versa; the two are difficult to balance, severely limiting the application of hard carbon anodes in power storage scenarios. Meanwhile, low-temperature operating conditions place extremely stringent demands on the material's kinetic properties, further amplifying the aforementioned contradiction.
[0004] To improve the electrochemical performance of hard carbon, researchers have proposed various modification strategies, mainly including increasing the interlayer spacing of graphite to promote Na+. + Rapid intercalation in graphite domains and optimization of porous structures to enhance Na / Na ratio + The storage capacity of clusters within suitable pores, and the introduction of heteroatoms or defect sites such as N, S, and F to provide more charge adsorption active sites, all contribute to improving the capacity and rate performance of hard carbon.
[0005] However, the aforementioned modification methods still face significant challenges in meeting the requirements of low-temperature cycling. At low temperatures, the transport rate of ions in the electrolyte and electrode solid phase decreases drastically, and the reactivity of the electrode materials also declines significantly, leading to severe battery capacity decay and low charge-discharge efficiency, making it difficult to meet practical application requirements. Existing methods have limited effectiveness in improving the slow diffusion of sodium ions at low temperatures, becoming a key technical obstacle restricting the low-temperature application of hard carbon materials.
[0006] To improve low-temperature kinetic performance, existing technologies have proposed introducing metal components into hard carbon materials, i.e., combining metal salts with carbon materials through physical mixing or simple doping. While this method improves the kinetic properties of the material to some extent, the metal doping efficiency is extremely low, with only a small number of metal atoms replacing the carbon layer surface, failing to achieve uniform bulk doping. Furthermore, during charge and discharge, the expansion effect and side reactions of metal particles on the carbon layer surface are difficult to control effectively, thus deteriorating long-term cycle stability and failing to meet the requirements of practical applications and large-scale production.
[0007] Therefore, there is an urgent need to develop a modification method for hard carbon anode materials that balances low-temperature kinetic improvement with long-term cycling stability and is scalable. Summary of the Invention
[0008] The purpose of this application is to provide a hard carbon anode material and its preparation method, an anode sheet, and a sodium-ion battery to solve the above-mentioned problems.
[0009] To achieve the above objectives, the first aspect of this application provides a hard carbon anode material, including a core and a coating layer disposed on the surface of the core; The core comprises zinc-doped hard carbon anode material; The coating layer includes a manganese-doped carbon material, wherein the manganese-doped carbon material has a disordered carbon structure.
[0010] Optionally, the zinc content in the zinc-doped hard carbon anode material is 2%-5% by mass.
[0011] Optionally, the manganese content in the manganese-doped carbon material is 1%-3% by mass.
[0012] Optionally, the thickness of the coating layer is 5-20 nm; The particle size of the hard carbon anode material is 4.0-8.0 μm.
[0013] Optionally, the interlayer spacing of the zinc-doped hard carbon anode material is 0.38-0.42 nm; The carbon atoms in the main framework of the zinc-doped hard carbon anode material are chemically bonded together by C–O–C or C–C bonds.
[0014] A second aspect of this application provides a method for preparing the aforementioned hard carbon anode material, comprising: Zinc salt, a first organic carbon source, and a first solvent are mixed to obtain a first mixture. The first mixture is then mixed with acetic acid and heated to obtain a mixed solution. The mixed solution is subjected to a polymerization reaction, cooled, washed, and dried to obtain zinc-doped hard carbon precursor particles. Manganese salt, a second organic carbon source, and a second solvent are mixed to obtain a second mixture. The second mixture is then mixed with acetic acid and heated to obtain a manganese-doped carbon-coated solution. The zinc-doped hard carbon precursor particles and the manganese-doped carbon coating solution are mixed, hydrothermally coated, washed, and dried to obtain a third mixture; the third mixture is then heat-treated under an inert atmosphere to obtain the hard carbon anode material. The zinc salt includes at least one of zinc acetate, zinc gluconate, and zinc nitrate; The manganese salt includes at least one of manganese acetate, manganese gluconate, and manganese nitrate.
[0015] Optionally, the preparation method of the hard carbon anode material satisfies at least one of the following conditions: (1) The first organic carbon source and the second organic carbon source each independently include at least one of carbohydrate compounds, organic acids, organic polymers, nitrogen-containing compounds and biomass derivatives; (2) The first solvent and the second solvent each independently include organic solvents and / or inorganic solvents; (3) The mass ratio of the zinc salt to the first organic carbon source is 1:25-50; the mass percentage of solids in the first mixture is 20-40%; (4) The mass ratio of the manganese salt to the second organic carbon source is 1:30-100, and the mass percentage of the solid in the second mixture is 5-10%.
[0016] Optionally, the preparation method of the hard carbon anode material satisfies at least one of the following conditions: (1) The first organic carbon source and the second organic carbon source each independently include at least one of glucose, sucrose, lactose, citric acid, tartaric acid, polyethylene, polyaniline, phenolic resin, urea, melamine, chitosan, and lignin; (2) The inorganic solvent includes water; (3) The organic solvent includes at least one of ethylene glycol, ethylene glycol ether, propylene glycol, and butanediol.
[0017] Optionally, the preparation method of the hard carbon anode material satisfies at least one of the following conditions: (1) The pH values of the mixtures subjected to the first heating and the second heating are each independently 5-6; (2) The temperatures of the first heating and the second heating are each 60-80℃, and the time is 30-120min; (3) The polymerization reaction is carried out at a temperature of 120-150℃ for 1-3 hours; (4) The temperature of the hydrothermal coating is 120-150℃ and the time is 1-4h; (5) The inert gas in the inert atmosphere includes nitrogen and / or argon; (6) The heating rate of the heat treatment is 2-5℃ / min, the final temperature is 900-1200℃, and the holding time is 1-2h.
[0018] A third aspect of this application provides a negative electrode sheet, comprising the aforementioned hard carbon negative electrode material.
[0019] A fourth aspect of this application provides a sodium-ion battery, including the aforementioned negative electrode sheet.
[0020] Compared with the prior art, the beneficial effects of this application include: The hard carbon anode material provided in this application improves sodium storage capacity and rate performance by creating pores and expanding the layer through zinc doping, and enhances cycle stability by passivating defects and stabilizing the SEI film with manganese shell. It achieves the synergistic effect of manganese-doped carbon coating layer and zinc-doped hard carbon core, which can achieve the dual effect of "zinc core expansion to improve capacity and manganese shell stabilization to improve cycle performance". It avoids the performance shortcomings of single metal doping and is significantly better than pure zinc-doped or pure manganese-doped hard carbon materials, so as to solve the problems of rapid low-temperature cycle decay and difficulty in balancing capacity and cycle performance of existing hard carbon anodes.
[0021] The preparation method of hard carbon anode material provided in this application adopts a stepwise in-situ complexation + secondary carbonization process. First, zinc-doped hard carbon precursor particles (core) are prepared by pH control, and then manganese-doped carbon is coated and secondary carbonization is carried out to form a core-shell structure. During the heat treatment process, metal atoms interact with hard carbon, opening the local interlayer structure of hard carbon and adjusting the pore structure of the material.
[0022] The negative electrode sheet and sodium-ion battery provided in this application have the characteristics of high initial efficiency, stable cycle performance, and excellent rate capability, and can be widely used in the field of low-temperature energy storage sodium-ion batteries. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments will be briefly described below. It should be understood that the following drawings only show some embodiments of this application and should not be regarded as a limitation on the scope of this application.
[0024] Figure 1 A schematic diagram of the hard carbon anode material provided in this application; Figure 2 A schematic diagram of the sodium ion transport mechanism of the zinc-doped hard carbon anode material provided in this application; Figure 3 The XRD pattern of the hard carbon anode material provided in Example 1; Figure 4 The graph shows the charge and discharge test results of the sodium-ion battery provided in Example 1 at -40°C. Figure 5 A comparison chart of GITT test results for sodium-ion batteries provided in Example 1 and Comparative Example 1. Detailed Implementation
[0025] To address the issue of insufficient bonding force between metal atoms and carbon materials, and to simultaneously optimize the expansion effect and side reactions of metal atoms during cycling, this application proposes the following solution: First, the solution provided in this application will be explained in more detail as follows: The first aspect of this application provides a hard carbon anode material, including a core and a coating layer disposed on the surface of the core; The core comprises zinc-doped hard carbon anode material; The coating layer includes a manganese-doped carbon material, wherein the manganese-doped carbon material has a disordered carbon structure.
[0026] The structural diagram of the hard carbon anode material is shown below. Figure 1 As shown.
[0027] It is important to note that the core is doped with zinc to regulate the internal microstructure of hard carbon, thereby improving sodium storage capacity and material kinetics. Specifically, zinc ions coordinate with precursor hydroxyl and carboxyl groups, and during carbonization, some zinc atoms are embedded into the carbon framework as single atoms. Above 900℃, a portion of elemental zinc volatilizes in a controlled manner, generating interlayer stress within the carbon layer, expanding the carbon sheets, and moderately increasing the d002 interlayer spacing. This effect occurs within the material bulk and is well-suited to function within the core.
[0028] The coating layer is doped with manganese. Manganese ions can form stable coordination bonds with precursor hydroxyl / carboxyl groups, anchoring to highly active sites at the carbon edge during carbonization. This passivates active defects at the carbon edge, reduces continuous side reactions in the electrolyte, and solves the problem of high surface defects in pure hard carbon, which leads to continuous electrolyte consumption and repeated damage to the SEI film during long cycles, resulting in capacity decline. Furthermore, the moderate atomic radius of manganese can appropriately increase the interlayer spacing of hard carbon d002 during carbonization, thereby reducing the Na+ content. + The embedding resistance alleviates the localized micro-expansion caused by repeated sodium embedding.
[0029] In some embodiments, the zinc content in the zinc-doped hard carbon anode material is 2%-5% by mass.
[0030] Optionally, the mass percentage of zinc in the zinc-doped hard carbon anode material can be any value between 2%, 3%, 4%, 5%, or 2-5%.
[0031] In some embodiments, the manganese content in the manganese-doped carbon material is 1%-3% by mass.
[0032] Optionally, the mass percentage of manganese in the manganese-doped carbon material can be 1%, 2%, 3%, or any value between 1% and 3%. In some embodiments, the thickness of the coating layer is 5-20 nm; Optionally, the thickness of the coating layer can be any value between 5 nm, 10 nm, 15 nm, 20 nm, or 5-20 nm; The particle size of the hard carbon anode material is 4.0-8.0 μm.
[0033] Optionally, the particle size of the hard carbon anode material can be any value between 4μm, 5μm, 6μm, 7μm, 8μm or 4-8μm.
[0034] In some embodiments, the interlayer spacing of the zinc-doped hard carbon anode material is 0.38-0.42 nm; Optionally, the interlayer spacing of the zinc-doped hard carbon anode material can be any value between 0.38 nm, 0.39 nm, 0.40 nm, 0.41 nm, 0.42 nm, or 0.38-0.42 nm. It should be noted that hard carbon anode materials have a large interlayer spacing, excellent high ion transport speed, and excellent sodium storage performance and low-temperature cycling stability. The bimetallic doped hard carbon material prepared in this application has a graphite microcrystalline structure with a larger interlayer distance (d002 = 0.37~0.42nm) and a suitable nanoporous structure. Secondly, the manganese coating layer on the surface of the hard carbon anode material can not only reduce irreversible defects on the hard carbon surface and inhibit the continuous decomposition of the electrolyte, but also make the SEI film denser and more stable, thus constructing a dynamic interface for rapid sodium ion storage. The carbon atoms in the main framework of the zinc-doped hard carbon anode material are chemically bonded together by C–O–C or C–C bonds.
[0035] It should be noted that the sodium ion transport mechanism of the zinc-doped hard carbon anode material provided in this application is illustrated as follows: Figure 2 As shown in the figure, the zinc-doped metal of this application undergoes a coordination reaction with the hydroxyl and carboxyl groups in the carbon precursor, causing the metal atoms to embed into the carbon layer. During the charging and discharging process, the outermost electrons of the Zn atoms will shift, generating a certain Coulomb force, which pulls sodium ions, thereby reducing the diffusion barrier of sodium ions between graphite microcrystals, accelerating the storage kinetics of sodium ions, and ultimately improving the ultra-high rate performance and low-temperature cycle stability of sodium-ion batteries.
[0036] Under high temperature and high pressure conditions, processes such as coordination, coating, and carbonization are completed.
[0037] A second aspect of this application provides a method for preparing the aforementioned hard carbon anode material, comprising: Zinc salt, a first organic carbon source, and a first solvent are mixed to obtain a first mixture. The first mixture is then mixed with acetic acid and heated to obtain a mixed solution. The mixed solution is subjected to a polymerization reaction, cooled, washed, and dried to obtain zinc-doped hard carbon precursor particles. Manganese salt, a second organic carbon source, and a second solvent are mixed to obtain a second mixture. The second mixture is then mixed with acetic acid and heated to obtain a manganese-doped carbon-coated solution. The zinc-doped hard carbon precursor particles and the manganese-doped carbon coating solution are mixed, hydrothermally coated, washed, and dried to obtain a third mixture; the third mixture is then heat-treated under an inert atmosphere to obtain the hard carbon anode material. The zinc salt includes at least one of zinc acetate, zinc gluconate, and zinc nitrate; The manganese salt includes at least one of manganese acetate, manganese gluconate, and manganese nitrate.
[0038] It should be noted that by coating zinc-doped hard carbon precursor particles, this application can suppress the expansion effect and side reactions of zinc metal atoms during cycling, improve the stability of the material, and form a metal-doped hard carbon structure (third mixture). In subsequent heat treatment (pyrolysis carbonization), the sodium storage performance of the material can be improved by controlling the carbonization process and the synergistic effect of metal atoms.
[0039] Specifically, the synergistic effect of manganese metal atoms and organic carbon sources is as follows: during the carbonization process, the introduced manganese metal atoms will form Mn O The C cross-linking bonds anchor to highly active sites at the carbon edge, passivating carbon edge activity defects and reducing side reactions with the electrolyte during subsequent cycles. Simultaneously, the manganese doping in the coating layer does not volatilize and create pores like zinc, preventing the formation of numerous open micropores on the outer surface and avoiding irreversible sodium ion adsorption, thus contributing to maintaining a high initial coulombic efficiency.
[0040] In some embodiments, the method for preparing the hard carbon anode material satisfies at least one of the following conditions: (1) The first organic carbon source and the second organic carbon source each independently include at least one of carbohydrate compounds, organic acids, organic polymers, nitrogen-containing compounds and biomass derivatives; (2) The first solvent and the second solvent each independently include organic solvents and / or inorganic solvents; (3) The mass ratio of the zinc salt to the first organic carbon source is 1:25-50; the mass percentage of solids in the first mixture is 20-40%; Optionally, the mass ratio of zinc salt to the first organic carbon source can be any value between 1:25, 1:30, 1:35, 1:40, 1:45, 1:50 or 1:25-50, and the mass percentage of solids in the first mixture can be any value between 20%, 30%, 40% or 20-40%. (4) The mass ratio of the manganese salt to the second organic carbon source is 1:30-100, and the mass percentage of the solid in the second mixture is 5-10%.
[0041] Optionally, the mass ratio of manganese salt to the second organic carbon source can be any value between 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100 or 1:30-100, and the mass percentage of solids in the second mixture can be any value between 5%, 6%, 7%, 8%, 9%, 10% or 5-10%.
[0042] In some embodiments, the method for preparing the hard carbon anode material satisfies at least one of the following conditions: (1) The first organic carbon source and the second organic carbon source each independently include at least one of glucose, sucrose, lactose, citric acid, tartaric acid, polyethylene, polyaniline, phenolic resin, urea, melamine, chitosan, and lignin; (2) The inorganic solvent includes water; (3) The organic solvent includes at least one of ethylene glycol, ethylene glycol ether, propylene glycol, and butanediol.
[0043] In some embodiments, the method for preparing the hard carbon anode material satisfies at least one of the following conditions: (1) The pH values of the mixtures subjected to the first heating and the second heating are each independently 5-6; Optionally, the pH values of the mixtures subjected to the first and second heating can each be independently 5, 5.5, 6, or any value between 5 and 6; (2) The temperatures of the first heating and the second heating are each 60-80℃, and the time is 30-120min; Optionally, the temperatures of the first heating and the second heating can be independently set to 60℃, 70℃, 80℃ or any value between 60℃ and 80℃, and the time can be any value between 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min or 30 min and 120 min. (3) The polymerization reaction is carried out at a temperature of 120-150℃ for 1-3 hours; Optionally, the polymerization temperature can be any value between 120℃, 130℃, 140℃, 150℃ or 120-150℃, and the time can be any value between 1h, 2h, 3h or 1-3h. (4) The temperature of the hydrothermal coating is 120-150℃ and the time is 1-4h; Optionally, the hydrothermal coating temperature can be any value between 120℃, 130℃, 140℃, 150℃ or 120-150℃, and the time can be any value between 1h, 2h, 3h, 4h or 1-4h. (5) The inert gas in the inert atmosphere includes nitrogen and / or argon; (6) The heating rate of the heat treatment is 2-5℃ / min, the final temperature is 900-1200℃, and the holding time is 1-2h.
[0044] Optionally, the heating rate of the heat treatment can be any value between 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min or 2-5℃ / min, the final temperature can be any value between 900℃, 1000℃, 1100℃, 1200℃ or 900-1200℃, and the isothermal time can be any value between 1h, 1.5h, 2h or 1-2h.
[0045] A third aspect of this application provides a negative electrode sheet, comprising the aforementioned hard carbon negative electrode material.
[0046] In some embodiments, the specific capacity of the negative electrode can reach 542 mAh / g, the low-temperature cycle life is improved to over 500T, the discharge specific capacity at -40℃ can reach 422 mAh / g, and the room temperature cycle life is improved to over 1500T.
[0047] A fourth aspect of this application provides a sodium-ion battery, including the aforementioned negative electrode sheet.
[0048] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0049] Example 1 The first aspect of this embodiment provides a hard carbon anode material, including a core and a coating layer disposed on the surface of the core; The core includes zinc-doped hard carbon anode material; The coating layer includes manganese-doped carbon material, wherein the manganese-doped carbon material has a disordered carbon structure.
[0050] The second aspect of this embodiment provides a method for preparing a hard carbon anode material, the specific steps of which are as follows: (1) Preparation of zinc-doped hard carbon precursor: 1.5g zinc acetate and 37.0g glucose first organic carbon source were dissolved in 100g water, and the pH of the solution was adjusted to 6.0 with acetic acid. After heating and stirring at 80℃ for 60 min, a mixture A was obtained. Then, the mixture A was transferred to a reactor for polymerization reaction at 120℃ for 2 h. After cooling, washing and drying, zinc-doped hard carbon precursor particles were obtained. (2) Preparation of manganese-doped carbon coating solution: Dissolve 0.2g manganese acetate and 7.5g glucose second organic carbon source in 100g water, and adjust the pH of the solution to 6.0 with acetic acid. Heat and stir at 80℃ for 60 min to obtain manganese-doped carbon coating solution; (3) Coating and secondary carbonization: The zinc-doped hard carbon powder obtained in step (1) is added to the manganese-doped carbon coating solution in step (2) and transferred to a reactor for hydrothermal coating reaction at a reaction temperature of 140°C and a reaction time of 3h; double-doped metal hard carbon material particles with core-shell structure are obtained; then washed and dried, and under inert gas protection, secondary carbonization is carried out at 1100°C for 2h, and after cooling, hard carbon anode material is obtained.
[0051] The XRD pattern of the hard carbon anode material is as follows: Figure 3 As shown.
[0052] The third aspect of this embodiment provides a negative electrode sheet, including the above-mentioned hard carbon negative electrode material.
[0053] The specific preparation method of this negative electrode sheet is as follows: (4) The hard carbon negative electrode material, conductive agent (SP) and binder (CMC, SBR) obtained in step (3) are mixed with deionized water in a mass ratio of 94.5:2:2:1.5 and then coated onto the current collector (copper foil) to make a sodium-ion battery negative electrode sheet. The fourth aspect of this embodiment provides a sodium-ion battery, including the above-mentioned negative electrode sheet.
[0054] The specific preparation method of this sodium-ion battery is as follows: (5) Using sodium sheet as positive electrode, aluminum foil as positive electrode current collector, Celgard2300 type separator as separator, 1 M NaPF6in Diglyme=100 vol% electrolyte produced by Nanjing Mojies Technology Co., Ltd. as electrolyte, and using the negative electrode sheet of step (4), the button cell is assembled in an argon glove drying oven (moisture content controlled below 15ppm).
[0055] This application also provides Examples 2-5 and Comparative Examples 1-5, the differences of which from Example 1 are shown in Table 1.
[0056] Table 1. Parameters of the Examples and Comparative Examples
[0057] This application follows the sodium-ion battery preparation method of Example 1, and uses the hard carbon anode materials provided in Examples 2-5 and Comparative Examples 1-5 to prepare corresponding sodium-ion batteries. The electrochemical performance of the batteries is tested using a computer-controlled tester. The charging current is 0.1C, the discharging current is 0.1C, the charging and discharging voltage range is 0~2.0V, and the current density is 30 mA / g. The specific test results are shown in Table 2.
[0058] Among them, the charge-discharge test results of the sodium-ion battery provided in Example 1 at -40°C are as follows: Figure 4 As shown.
[0059] Table 2 Electrochemical Performance Tests
[0060] This application also conducted GITT tests on the sodium-ion batteries provided in Example 1 and Comparative Example 1. The specific test results are shown in Table 3. Additionally, the GITT test results of the sodium-ion batteries provided in Example 1 and Comparative Example 1 are as follows: Figure 5 As shown in the figure (left figure is discharge GITT, right figure is charge GITT), the red curve represents Example 1, and the black curve represents Comparative Example 1. Example 1 has a larger ion diffusion coefficient and less polarization. The galvanostatic gap titration (GITT) test method is as follows: (1) Pulse current: 0.1 C, to ensure that the pulse current is small enough and the electrode polarization is in the linear range during the test process, satisfying the theoretical assumptions of GITT test; (2) Constant current pulse time: 30 min, to ensure that ions undergo limited diffusion within the electrode material during a single pulse process, meeting the short-time pulse test conditions (t << L). 2 / D, where L is the thickness of the electrode active layer and D is the ion diffusion coefficient). (3) Resting relaxation time: 60 min, no current input, allowing ions inside the electrode to diffuse fully, interface polarization to be completely eliminated, and the battery open circuit voltage to return to a balanced and stable state (voltage change rate ≤ 1 mV / min). Based on the voltage-time data acquired by GITT testing, the apparent ion diffusion coefficient of the electrode material is calculated using the following formula: ; In the formula: D is the apparent diffusion coefficient of ions, in cm. 2 ·s -1 ; τ is the duration of the constant current pulse, in seconds; m B The mass of the electrode active material is expressed in grams. V M The molar volume of the active substance is expressed in cm³. 3 ·mol -1 ; M B The molar mass of the active substance is expressed in g·mol⁻¹. -1 S represents the effective electrochemical active area of the electrode, in cm². 2 ; ΔEs is the difference in the battery's balanced open-circuit voltage before and after the pulse, in V; ΔEτ is the instantaneous voltage change difference of the battery during a single pulse process (excluding the balance voltage offset), in V.
[0061] Table 3 GITT Test
[0062] analyze: Based on the above tests, it can be seen that Examples 1-3 set up different zinc salts, manganese salts, organic carbon sources and different doping amounts for comparison, verifying the compatibility of different carbon sources and metal salts, and thus different capacities, first-efficiency and low-temperature performance. Specifically, Example 2, compared with Example 1, reduced zinc doping amount slightly reduced the interlayer spacing of the material, resulting in a slight decrease in specific capacity and a slight decrease in low-temperature performance of the material; Example 3, compared with Example 1, increased zinc doping amount further opened up the interlayer spacing of the material, thus affecting the first-efficiency and low-temperature cycle retention rate.
[0063] The hard carbon anode materials of Examples 1-5 were prepared by comparing zinc salt, manganese salt, organic carbon source and different doping amounts. The electrochemical performance of the batteries obtained was comparable to that of Example 1, and each had its own advantages, indicating that the method of this application is applicable to the comparison of zinc salt, manganese salt, organic carbon source and different doping amounts.
[0064] The hard carbon anode materials in Examples 4 and 5 were controlled by different coating amounts to obtain materials with different initial efficiency, specific capacity, and kinetic properties. Specifically, in Example 4, the coating amount was reduced, resulting in a decrease in initial efficiency, but an improvement in kinetic performance. In Example 5, the coating amount was increased, resulting in a simultaneous increase in initial efficiency and improved low-temperature stability, but a slight decrease in specific capacity.
[0065] Comparative Example 1, which did not add zinc salt and did not perform zinc doping during preparation, resulted in a hard carbon anode material with poor kinetic performance, which did not support low-temperature cycling and had a low capacity. This demonstrates that zinc doping is beneficial to improving the low-temperature performance and kinetic performance of the material, and the specific capacity of the material is also significantly improved.
[0066] Comparative Example 2, which did not undergo coating treatment, resulted in a significant reduction in the first-efficiency of the hard carbon anode material, demonstrating that coating can reduce side reactions and improve the first-coulomb efficiency of the material.
[0067] In Comparative Example 3, the absence of manganese doping during coating resulted in a significant decrease in cycling stability. However, compared to the uncoated sample in Comparative Example 2, the cycling stability was improved to some extent, indicating that coating can enhance the material structure and improve cycling performance. In addition, manganese doping can reduce the side reaction effects between hard carbon and electrolyte, delay SEI film growth, maintain interfacial stability, and thus ensure cycling stability.
[0068] The chloride and sulfate used in Comparative Examples 4 and 5 both had a certain negative impact on the material preparation. Specifically, chloride ions and sulfate ions are prone to remain in the preparation process and continuously react with the electrolyte during subsequent charge and discharge processes, resulting in a continuous increase in the charge transfer impedance of the material, affecting the stability of the material, and without significantly improving the capacity and kinetics.
[0069] In summary, the synergistic effect of the manganese-doped carbon coating layer and the zinc-doped hard carbon core in this application can achieve the dual effect of "expanding the zinc core to increase capacity and stabilizing the manganese shell to improve cycle life", avoiding the performance shortcomings of single metal doping and significantly outperforming pure zinc-doped or pure manganese-doped hard carbon materials.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0071] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, any of the claimed embodiments can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
Claims
1. A hard carbon anode material, characterized in that, Includes a core and a covering layer disposed on the surface of the core; The core comprises zinc-doped hard carbon anode material; The coating layer includes a manganese-doped carbon material, wherein the manganese-doped carbon material has a disordered carbon structure.
2. The hard carbon anode material according to claim 1, characterized in that, The zinc-doped hard carbon anode material contains 2%-5% zinc by mass. And / or, the mass percentage of manganese in the manganese-doped carbon material is 1%-3%.
3. The hard carbon anode material according to claim 1, characterized in that, The thickness of the coating layer is 5-20 nm; The particle size of the hard carbon anode material is 4.0-8.0 μm.
4. The hard carbon anode material according to any one of claims 1-3, characterized in that, The interlayer spacing of the zinc-doped hard carbon anode material is 0.38-0.42 nm; The carbon atoms in the main framework of the zinc-doped hard carbon anode material are chemically bonded together by C–O–C or C–C bonds.
5. A method for preparing the hard carbon anode material as described in any one of claims 1-4, characterized in that, include: Zinc salt, a first organic carbon source, and a first solvent are mixed to obtain a first mixture. The first mixture is then mixed with acetic acid and heated to obtain a mixed solution. The mixed solution is subjected to a polymerization reaction, cooled, washed, and dried to obtain zinc-doped hard carbon precursor particles. Manganese salt, a second organic carbon source, and a second solvent are mixed to obtain a second mixture. The second mixture is then mixed with acetic acid and heated to obtain a manganese-doped carbon-coated solution. The zinc-doped hard carbon precursor particles and the manganese-doped carbon coating solution are mixed, hydrothermally coated, washed, and dried to obtain a third mixture; the third mixture is then heat-treated under an inert atmosphere to obtain the hard carbon anode material. The zinc salt includes at least one of zinc acetate, zinc gluconate, and zinc nitrate; The manganese salt includes at least one of manganese acetate, manganese gluconate, and manganese nitrate.
6. The method for preparing the hard carbon anode material according to claim 5, characterized in that, At least one of the following conditions must be met: (1) The first organic carbon source and the second organic carbon source each independently include at least one of carbohydrate compounds, organic acids, organic polymers, nitrogen-containing compounds and biomass derivatives; (2) The first solvent and the second solvent each independently include organic solvents and / or inorganic solvents; (3) The mass ratio of the zinc salt to the first organic carbon source is 1:25-50; the mass percentage of solids in the first mixture is 20-40%; (4) The mass ratio of the manganese salt to the second organic carbon source is 1:30-100, and the mass percentage of the solid in the second mixture is 5-10%.
7. The method for preparing the hard carbon anode material according to claim 6, characterized in that, At least one of the following conditions must be met: (1) The first organic carbon source and the second organic carbon source each independently include at least one of glucose, sucrose, lactose, citric acid, tartaric acid, polyethylene, polyaniline, phenolic resin, urea, melamine, chitosan, and lignin; (2) The inorganic solvent includes water; (3) The organic solvent includes at least one of ethylene glycol, ethylene glycol ether, propylene glycol, and butanediol.
8. The method for preparing the hard carbon anode material according to any one of claims 5-7, characterized in that, At least one of the following conditions must be met: (1) The pH values of the mixtures subjected to the first heating and the second heating are each independently 5-6; (2) The temperatures of the first heating and the second heating are each 60-80℃, and the time is 30-120min; (3) The polymerization reaction is carried out at a temperature of 120-150℃ for 1-3 hours; (4) The temperature of the hydrothermal coating is 120-150℃ and the time is 1-4h; (5) The inert gas in the inert atmosphere includes nitrogen and / or argon; (6) The heating rate of the heat treatment is 2-5℃ / min, the final temperature is 900-1200℃, and the holding time is 1-2h.
9. A negative electrode sheet, characterized in that, Includes the hard carbon anode material as described in any one of claims 1-4.
10. A sodium-ion battery, characterized in that, Includes the negative electrode sheet as described in claim 9.
